84.7k views
4 votes
5x 2 +1=−13x−5 the two is an exponent for the 5x.

2 Answers

0 votes

Answer:

x=-6/23

Explanation:

User Tetranz
by
5.7k points
7 votes

Answer:

x = - 2, x = -
(3)/(5)

Explanation:

Given

5x² + 1 = - 13x - 5 ( add 13x - 5 to both sides )

5x² + 13x + 6 = 0

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term

product = 5 × 6 = 30 and sum = 13

The factors are 10 and 3

Use these factors to split the x- term

5x² + 10x + 3x + 6 = 0 ( factor the first/second and third/fourth terms )

5x(x + 2) + 3(x + 2) = 0 ← factor out (x + 2) from each term

(x + 2)(5x + 3) = 0

Equate each factor to zero and solve for x

x + 2 = 0 ⇒ x = - 2

5x + 3 = 0 ⇒ 5x = - 3 ⇒ x = -
(3)/(5)

User JanuszO
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.